Stock market volatility during post-crisis, case of US S&P500 - Elmguirhi, Sonia (JAAF (Journal of Applied Accounting and Finance), 2025)
This study examines the volatility of market indices and derivatives. This created a major impact on the financial system. This impact appeared in a big way during the last financial crisis of 2008 which is still felt even until now. Using daily closing price from S&P500 stock index starting from 2005 to 2009, and 2015 to 2022, graphical and regression analysis (OLS) and DCC-GARCH a are used to explore the volatility of the stocks. The findings show that the financial market is highly interconnected, and an inverse relationship between the S&P 500 and the VIX occur, with the VIX rising significantly during post-crisis periods when the S&P 500 is low, indicating market stress and volatility. It implies that growing systemic risks, fueled by complex and poorly regulated financial instruments, may lead to future financial crises driven by contagion and market imbalances.